Rampage [videorecording (DVD)] - Peyton, Brad, 1979-; Peyton, Brad, 1979-; Johnson, Dwayne, 1972-; Morgan, Jeffrey Dean, 1966-; Harris, Naomie, 1976- (Warner Bros. Entertainment, 2018)
A primatologist and a geneticist team up to try to save the city of Chicago when animals become infected with a dangerous pathogen and wreak havoc on the town.